Anti-static high-pressure-resistant PPR (polypropylene random copolymer) material and preparation method thereof

By adding pre -processed aluminum -plated glass fiber, carbon nano fiber, β nuclear, and α nuclear agent to the PPR material, and the heating and shear treatment of the extruder, the PPR material anti -static performance and The problem of poor mechanical performance has achieved significant performance improvement and application expansion.

CN119350768AInactive Publication Date: 2025-01-24RIFENG ENTERPRISE (TIANJIN) CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411918704.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The poor anti-static and mechanical properties of existing PPR materials limit their application in the industrial field.

Method used

By adding pre -processed aluminum -plated glass fiber, carbon nano fiber, β nuclear, and α nuclear agent to the PPR material, and heating and cutting are formed in the extruder to form a conductive network to improve the anti -static performance And mechanical performance.

Benefits of technology

It significantly improves the anti -static performance of PPR materials, electromagnetic wave shielding performance and mechanical performance, and expanded its application scope in the industrial field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an anti-static high-pressure-resistant PPR material and a preparation method thereof, and belongs to the field of PPR material preparation. The aluminized glass fibers are pretreated through the composite antistatic agent and the coupling agent, electrostatic adsorption among the aluminized glass fibers can be reduced, the dispersity of the aluminized glass fibers in a PPR matrix is improved, the antistatic effect of the aluminized glass fibers in the PPR material can be brought into play, and the antistatic effect of the aluminized glass fibers in the PPR material can be improved through interaction of the aluminized glass fibers of different sizes. The mechanical property of the PPR material is favorably improved. The beta nucleating agent and the alpha nucleating agent are added to achieve a synergistic effect, the effect of adjusting rigidity and toughness balance of the PPR material is achieved under the condition of not additionally adding a toughening agent, the crystal form of the PPR material is adjusted and controlled by combining subsequent heating temperature control in an extruding machine, and then the PPR material interacts with the aluminized glass fibers, the carbon nanofibers and the wear-resisting agent, so that the wear-resisting property of the PPR material is improved. Therefore, the PPR material has remarkable anti-static performance, electromagnetic wave shielding performance and mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of PPR material preparation, and in particular to an antistatic and high-voltage resistant PPR material and a preparation method thereof. Background Art

[0002] Conventional polypropylene (PP) has problems such as high low-temperature brittleness and poor creep performance, which are not conducive to its use in pipelines. For this reason, R&D personnel have successively developed different types of special materials for polypropylene pipes: for example, the first generation of special pipe materials (PPH, homopolymer grade) is mainly used for the discharge of industrial sewage; the second generation of special pipe materials (PPB, block copolymer grade) is mainly used for drainage and sewage; the third generation of special pipe materials (PPR, random copolymer grade) is mainly used for hot water supply, floor heating and snow melting systems, etc. It is an ideal product for modern industrial pipeline systems and is favored by the market.

[0003] In the prior art, polypropylene products themselves cannot meet the use requirements, and often need to be blended, filled and modified to obtain functional composite materials with different properties, such as antistatic, electrical conductivity, aging resistance, etc. For example, the Chinese invention patent application number 201910468222.9 discloses a method for preparing thermoplastic resin-based composite materials. Polypropylene is modified by nano-mullite and chopped glass fibers. Although the mechanical properties of the polypropylene matrix are greatly improved, it does not have antistatic properties. For example, the Chinese patent application number CN202410166715.8 discloses an antistatic plastic pipe, pipe fittings, valves and their preparation methods. By adding a carbon black conductive agent, the extruded pipe has antistatic properties, but the untreated carbon black conductive agent has poor dispersibility and will also affect the antistatic performance. For example, Chinese patent application number CN202410035539.4 discloses a method for preparing an antistatic polypropylene material and the application of the resulting antistatic polypropylene material. The antistatic material is obtained by melting, extruding and granulating components such as polypropylene, silica nanotubes loaded with ionic liquid, a compatibilizer and a lubricant, but it cannot simultaneously meet the use requirements of antistatic and mechanical properties.

[0004] Therefore, there are still problems in the prior art that need to be solved, such as poor antistatic performance, poor pressure resistance and low strength of PPR materials, which limit their application. Summary of the invention

[0005] Based on this, in order to solve the technical problems of poor antistatic performance and mechanical properties of PPR materials prepared in the prior art, the present invention provides an antistatic high-voltage resistant PPR material and a preparation method thereof. The specific technical scheme is as follows: An antistatic high-voltage PPR material comprises the following raw materials in parts by weight: 100 parts of random copolymer polypropylene, 5 to 30 parts of aluminum-plated glass fiber, 1 to 3 parts of carbon nanofiber, 0.1 to 0.3 parts of β-nucleating agent, 0.01 to 0.03 parts of α-nucleating agent, 1 to 3 parts of compatibilizer and 1 to 3 parts of wear-resistant agent; Wherein, the aluminum-plated glass fiber is pre-treated with a treatment agent, and the treatment agent includes a composite antistatic agent and a coupling agent.

[0006] Furthermore, the composite antistatic agent is obtained by mixing ethoxylated amine and graphene oxide in a mass ratio of (0.01-0.08):(1-7).

[0007] Furthermore, the coupling agent is at least one of γ-glycidyloxypropyltrimethoxysilane, triaminopropyltriethoxysilane and titanate coupling agent.

[0008] Furthermore, the pretreatment is: adding a coupling agent to a glacial acetic acid solution with a mass percentage concentration of 1% to 2%, then adding a composite antistatic agent and mixing to obtain a treatment agent, then adding aluminum-plated glass fiber to the treatment agent, adding a dispersant, and ultrasonically dispersing at 85°C to 100°C for 10min to 30min.

[0009] Furthermore, the diameter of the aluminum-plated glass fiber is 15 μm to 30 μm, the thickness of the aluminum-plated layer is 1 μm to 5 μm, and the purity of aluminum is greater than 99%.

[0010] Furthermore, the specifications of the aluminum-coated glass fiber include grade A, grade B and grade C, wherein the average length of grade A is 5μm~10μm, the average length of grade B is 11μm~25μm, the average length of grade C is 35μm~40μm, and the mass ratio of grade A, grade B and grade C is (1~5):(3~15):(1~3).

[0011] Furthermore, the compatibilizer is polypropylene grafted with maleic anhydride.

[0012] Furthermore, the anti-wear agent is siloxane, and the molecular weight of the siloxane is in the range of 2w~6w. Furthermore, the dispersant is hexadecyltrimethylammonium bromide.

[0013] In addition, the present application also provides a method for preparing an anti-static high-voltage PPR material, the preparation method comprising the following steps: The random copolymer polypropylene, aluminum-coated glass fiber, carbon nanofiber, β nucleating agent, α nucleating agent, compatibilizer and wear-resistant agent are mixed, and the temperature is increased to 180°C~220°C at a heating rate of 10°C / min~15°C / min, and the temperature is kept constant for 5min~10min. Then, the temperature is quickly reduced to 100°C~110°C at a cooling rate of 20°C / min~30°C / min, and the temperature is kept constant for 5min~10min, so that the mixed raw materials are heated and sheared in the extruder, and then melt-extruded, cooled, and formed to obtain an antistatic and high-pressure-resistant PPR material.

[0014] Compared with the prior art, the beneficial effects of this application include the following: 1. The present application pre-treats the aluminum-plated glass fiber by using a composite antistatic agent and a coupling agent. While ensuring the conductive properties of the aluminum-plated glass fiber, it can effectively solve the problem of electrostatic adsorption between the aluminum-plated glass fibers, improve its dispersibility and compatibility in the PPR matrix, and help to exert its antistatic effect in the PPR material.

[0015] 2. The present application adds pretreated aluminum-coated glass fibers of different sizes to the PPR matrix, utilizing the interaction between aluminum-coated glass fibers of different sizes to increase the mutual contact between the aluminum-coated glass fibers, which not only makes it easier for them to overlap with each other in the matrix to form a conductive network, but also helps to improve the mechanical properties of the PPR material.

[0016] 3. The present application adds a two-component nucleating agent, β-nucleating agent and α-nucleating agent, which work synergistically to adjust the balance between the rigidity and toughness of the PPR matrix without the need to add additional toughening agents. Combined with subsequent processing technology and heating temperature control in the extruder, the crystal morphology of the PPR material can be regulated. The interaction with aluminum-coated glass fiber, carbon nanofiber and wear-resistant agent can reduce the surface resistance of the PPR material, so that the PPR material has significant anti-static properties, electromagnetic wave shielding properties and mechanical properties, expanding its application range in the industrial field. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the protection scope of the present invention.

[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0019] An antistatic high-voltage PPR material in one embodiment of the present invention comprises the following raw materials in parts by weight: 100 parts of random copolymer polypropylene, 5 to 30 parts of aluminum-plated glass fiber, 1 to 3 parts of carbon nanofiber, 0.1 to 0.3 parts of β-nucleating agent, 0.01 to 0.03 parts of α-nucleating agent, 1 to 3 parts of compatibilizer and 1 to 3 parts of wear-resistant agent; Wherein, the aluminum-plated glass fiber is pre-treated with a treating agent, and the treating agent includes a composite antistatic agent and a coupling agent.

[0020] In one embodiment, the composite antistatic agent is obtained by mixing ethoxylated amine and graphene oxide in a mass ratio of (0.01-0.08):(1-7).

[0021] In one embodiment, the coupling agent is at least one of γ-glycidyloxypropyltrimethoxysilane, triaminopropyltriethoxysilane and titanate coupling agent.

[0022] In one embodiment, the pretreatment is: adding a coupling agent to a glacial acetic acid solution with a mass percentage concentration of 1% to 2%, then adding a composite antistatic agent and mixing to obtain a treatment agent, then adding aluminum-plated glass fiber to the treatment agent, adding a dispersant, and ultrasonically dispersing at 85°C to 100°C for 10min to 30min.

[0023] In one embodiment, the amount of the coupling agent added is 5% to 15% of the volume of the treating agent.

[0024] In one embodiment, the added amount of the composite antistatic agent accounts for 1% to 3% of the volume of the treatment agent.

[0025] In one embodiment, the amount of the dispersant added is 0.5% to 0.8% of the volume of the treatment agent.

[0026] In one of the embodiments, the liquid ratio of the aluminum-coated glass fiber to the treating agent is (1 g~10 g) / (10 mL~100 mL).

[0027] In one of the embodiments, the diameter of the aluminum-plated glass fiber is 15 μm to 30 μm, the thickness of the aluminum-plated layer is 1 μm to 5 μm, and the purity of aluminum is greater than 99%.

[0028] In one embodiment, the specifications of the aluminum-plated glass fiber include grade A, grade B and grade C, wherein the average length of grade A is 5μm~10μm, the average length of grade B is 11μm~25μm, the average length of grade C is 35μm~40μm, and the mass ratio of grade A, grade B and grade C is (1~5):(3~15):(1~3). The present invention can reduce the problem of entanglement and poor dispersion of aluminum-plated glass fibers in the matrix by adding aluminum-plated glass fibers of limited specifications. Aluminum-plated glass fibers of different specifications interact with each other, and aluminum-plated glass fibers are not easy to break during mixing. Shorter aluminum-plated glass fibers are filled between longer aluminum-plated glass fibers, making it easier to overlap each other in the matrix to form a conductive network, which also helps to improve the stability of the mechanical properties of PPR materials.

[0029] In one embodiment, the β-nucleating agent is 3,5-di(cyclohexylamide)-1-benzoic acid.

[0030] In one embodiment, the α nucleating agent is at least one of 1,3,5-benzene trimethylene glycol (cyclohexylamine) and 1,3,5-benzene trimethylene glycol (aniline). The β nucleating agent of the present invention refines the grain size, improves the toughness of the PPR material from a microscopic perspective, and improves the compressive strength. Adding an α nucleating agent can help improve the problem of reduced tensile strength caused by the β nucleating agent. Adding a limited ratio of β nucleating agent and α nucleating agent can obtain a PPR material with better mechanical properties. In one embodiment, the compatibilizer is polypropylene grafted maleic anhydride.

[0031] In one embodiment, the anti-wear agent is siloxane, and the molecular weight of the siloxane is in the range of 2w~6w. In one embodiment, the dispersant is hexadecyltrimethylammonium bromide.

[0032] In addition, the present application also provides a method for preparing an anti-static high-voltage PPR material, the preparation method comprising the following steps: Random copolymerized polypropylene, aluminum-plated glass fiber, carbon nanofiber, β nucleating agent, α nucleating agent, compatibilizer and wear-resistant agent are mixed, heated to 180℃~220℃ at a heating rate of 10℃ / min~15℃ / min, kept at a constant temperature for 5min~10min, then quickly cooled to 100℃~110℃ at a cooling rate of 20℃ / min~30℃ / min, kept at a constant temperature for 5min~10min, so that the mixed raw materials are heated and sheared in an extruder, melt-extruded, cooled, and molded to obtain an antistatic high-pressure PPR material. The present invention can promote uniform crystallization by heating and shearing in an extruder.

[0033] In one embodiment, in the melt extrusion process, the temperature of the extruder barrel is 210°C-225°C, and the temperature of the die head is 230°C-235°C.

[0034] In one embodiment, the pulling speed into the vacuum sizing cooling water tank is 10m / min-15m / min, and the temperature of the cooling water tank is 20°C.

[0035] The PPR material prepared by the above scheme has significant antistatic properties and mechanical properties.

[0036] The embodiments of the present invention will be described in detail below with reference to specific examples.

[0037] Embodiment 1: An antistatic high-voltage PPR material includes the following raw materials in parts by weight: 100 parts of random copolymer polypropylene, 13 parts of aluminum-coated glass fiber, 2 parts of carbon nanofiber, 0.2 parts of 3,5-di(cyclohexylamide)-1-benzoic acid, 0.03 parts of 1,3,5-benzenetricarboxylic acid tri(cyclohexylamine), 2 parts of polypropylene grafted maleic anhydride and 2 parts of siloxane; Among them, the diameter of the aluminum-coated glass fiber is 20μm, the thickness of the aluminum coating is 3μm, and the purity of aluminum is >99%; the specifications of the aluminum-coated glass fiber include grade A, grade B and grade C, among which the average length of grade A is 5μm, the average length of grade B is 20μm, the average length of grade C is 40μm, and the mass ratio of grade A, grade B and grade C is 5:13:3.

[0038] A method for preparing an anti-static high-voltage PPR material comprises the following steps: Ethoxyamine and graphene oxide in a mass ratio of 0.05:2 are mixed to obtain a composite antistatic agent, and then triaminopropyl triethoxysilane in an amount accounting for 12% by volume of the treating agent is added to a glacial acetic acid solution with a mass percentage concentration of 2%, and the composite antistatic agent in an amount accounting for 3% by volume of the treating agent is added, and the treating agent is obtained after mixing; The aluminum-plated glass fiber is added to the treatment agent at a material-liquid ratio of 1 g / 10 mL, and then 0.5% of the volume of the treatment agent is added with hexadecyltrimethylammonium bromide, and ultrasonically dispersed at 85° C. for 30 minutes to obtain the pretreated aluminum-plated glass fiber; The random copolymer polypropylene, pretreated aluminum-coated glass fiber, carbon nanofiber, 3,5-di(cyclohexylamide)-1-benzoic acid, 1,3,5-benzenetricarboxylic acid tri(cyclohexylamine), polypropylene grafted maleic anhydride and siloxane are mixed, the temperature is increased to 180°C at a heating rate of 10°C / min, the temperature is kept constant for 5 minutes, and then the temperature is quickly reduced to 100°C at a cooling rate of 20°C / min, and the temperature is kept constant for 5 minutes, so that the mixed raw materials are heated and sheared in the extruder, and then melt-extruded with the temperature of the extruder barrel at 220°C and the die head temperature at 230°C. The mixed raw materials enter the vacuum sizing cooling water tank at a traction speed of 10m / min, and the temperature of the cooling water tank is 20°C. After molding, an antistatic and high-pressure-resistant PPR material is obtained.

[0039] Embodiment 2: An antistatic high-voltage PPR material includes the following raw materials in parts by weight: 100 parts of random copolymer polypropylene, 15 parts of aluminum-coated glass fiber, 1 part of carbon nanofiber, 0.3 parts of 3,5-di(cyclohexylamide)-1-benzoic acid, 0.01 parts of 1,3,5-benzenetricarboxylic acid tri(cyclohexylamine), 3 parts of polypropylene grafted maleic anhydride and 3 parts of siloxane; Among them, the diameter of the aluminum-coated glass fiber is 20μm, the thickness of the aluminum coating is 3μm, and the purity of aluminum is >99%; the specifications of the aluminum-coated glass fiber include grade A, grade B and grade C, among which the average length of grade A is 6μm, the average length of grade B is 22μm, the average length of grade C is 39μm, and the mass ratio of grade A, grade B and grade C is 5:13:3.

[0040] A method for preparing an anti-static high-voltage PPR material comprises the following steps: Ethoxyamine and graphene oxide in a mass ratio of 0.07:3 are mixed to obtain a composite antistatic agent, and then triaminopropyl triethoxysilane in an amount of 15% by volume of the treating agent is added to a glacial acetic acid solution with a mass percentage concentration of 2%, and the composite antistatic agent in an amount of 3% by volume of the treating agent is added, and the treating agent is obtained after mixing; The aluminum-plated glass fiber is added to the treatment agent at a material-liquid ratio of 1 g / 10 mL, and then hexadecyltrimethylammonium bromide accounting for 0.8% of the volume of the treatment agent is added, and ultrasonic dispersion is performed at 90° C. for 30 minutes to obtain the pretreated aluminum-plated glass fiber; The random copolymer polypropylene, pretreated aluminum-coated glass fiber, carbon nanofiber, 3,5-di(cyclohexylamide)-1-benzoic acid, 1,3,5-benzenetricarboxylic acid tri(cyclohexylamine), polypropylene grafted maleic anhydride and siloxane are mixed, the temperature is increased to 200°C at a heating rate of 12°C / min, the temperature is kept constant for 6 minutes, and then the temperature is quickly reduced to 100°C at a cooling rate of 20°C / min, and the temperature is kept constant for 5 minutes, so that the mixed raw materials are heated and sheared in the extruder, and then melt-extruded with the temperature of the extruder barrel at 220°C and the die head temperature at 230°C. The mixed raw materials enter the vacuum sizing cooling water tank at a traction speed of 11m / min, and the temperature of the cooling water tank is 20°C, and the mixed raw materials are formed to obtain an antistatic and high-pressure-resistant PPR material.

[0041] Embodiment 3: An antistatic high-voltage PPR material includes the following raw materials in parts by weight: 100 parts of random copolymer polypropylene, 18 parts of aluminum-coated glass fiber, 1 part of carbon nanofiber, 0.3 parts of 3,5-di(cyclohexylamide)-1-benzoic acid, 0.02 parts of 1,3,5-benzenetricarboxylic acid tri(aniline), 2 parts of polypropylene grafted maleic anhydride and 3 parts of siloxane; Among them, the diameter of the aluminum-coated glass fiber is 20μm, the thickness of the aluminum coating is 3μm, and the purity of aluminum is >99%; the specifications of the aluminum-coated glass fiber include grade A, grade B and grade C, among which the average length of grade A is 10μm, the average length of grade B is 25μm, the average length of grade C is 40μm, and the mass ratio of grade A, grade B and grade C is 5:13:3.

[0042] A method for preparing an anti-static high-voltage PPR material comprises the following steps: Ethoxyamine and graphene oxide in a mass ratio of 0.08:7 are mixed to obtain a composite antistatic agent, and then triaminopropyl triethoxysilane in an amount of 15% by volume of the treating agent is added to a glacial acetic acid solution with a mass percentage concentration of 2%, and the composite antistatic agent in an amount of 3% by volume of the treating agent is added, and the treating agent is obtained after mixing; The aluminum-plated glass fiber is added to the treatment agent at a material-liquid ratio of 1 g / 10 mL, and then 0.8% of the volume of the treatment agent is added with hexadecyltrimethylammonium bromide, and ultrasonic dispersion is performed at 100° C. for 25 minutes to obtain the pretreated aluminum-plated glass fiber; The random copolymer polypropylene, pretreated aluminum-coated glass fiber, carbon nanofiber, 3,5-di(cyclohexylamide)-1-benzoic acid, 1,3,5-benzenetricarboxylic acid tri(aniline), polypropylene grafted maleic anhydride and siloxane are mixed, the temperature is increased to 210°C at a heating rate of 10°C / min, the temperature is kept constant for 5 minutes, and then the temperature is quickly reduced to 105°C at a cooling rate of 22°C / min, and the temperature is kept constant for 5 minutes, so that the mixed raw materials are heated and sheared in the extruder, and then melt-extruded with the temperature of the extruder barrel at 220°C and the die head at 230°C. The mixed raw materials enter the vacuum sizing cooling water tank at a traction speed of 15m / min, and the temperature of the cooling water tank is 20°C, and the mixed raw materials are formed to obtain an antistatic and high-pressure-resistant PPR material.

[0043] Comparative Example 1: The difference between Comparative Example 1 and Example 3 is that the specifications of the aluminum-coated glass fiber in Comparative Example 1 are as follows: the specifications of the aluminum-coated glass fiber include Grade A and Grade B, wherein the average length of Grade A is 30 μm, the average length of Grade B is 45 μm, and the mass ratio of Grade A to Grade B is 8:13; the others are the same as Example 3.

[0044] Comparative Example 2: The difference between Comparative Example 2 and Example 3 is that the specifications of the aluminum-coated glass fiber in Comparative Example 2 are as follows: the specifications of the aluminum-coated glass fiber include Grade A and Grade B, wherein the average length of Grade A is 55 μm, the average length of Grade B is 100 μm, and the mass ratio of Grade A to Grade B is 5:16; the others are the same as Example 3.

[0045] Comparative Example 3: The difference between Comparative Example 3 and Example 3 is that the aluminum-coated glass fiber in Comparative Example 3 is not pretreated, and the rest is the same as Example 3.

[0046] Comparative Example 4: The difference between Comparative Example 4 and Example 3 is that in Comparative Example 4, the aluminum-plated glass fiber is only treated with triaminopropyltriethoxysilane (without adding a composite antistatic agent), and the rest is the same as Example 3.

[0047] Comparative Example 5: The difference between Comparative Example 5 and Example 3 is that in Comparative Example 5, only a composite antistatic agent (without a coupling agent) is added to the treating agent of the aluminum-plated glass fiber, and the rest is the same as Example 3.

[0048] Comparative Example 6: The difference between Comparative Example 6 and Example 3 is that a single ethoxylated amine component is added to the treating agent for the aluminum-plated glass fiber in Comparative Example 6, and no graphene oxide is added. The rest is the same as Example 3.

[0049] Comparative Example 7: The difference between Comparative Example 7 and Example 3 is that in Comparative Example 7, no 3,5-di(cyclohexylamide)-1-benzoic acid is added, that is, no β-nucleating agent is added, and the rest is the same as Example 3.

[0050] Comparative Example 8: The difference between Comparative Example 8 and Example 3 is that in Comparative Example 8, no 1,3,5-benzenetricarboxylic acid tri(aniline) is added, that is, no α-nucleating agent is added, and the rest is the same as Example 3.

[0051] Comparative Example 9: The difference between Comparative Example 9 and Example 3 is that no siloxane (anti-wear agent) is added in Comparative Example 9, and the rest is the same as Example 3.

[0052] Comparative Example 10: The difference between Comparative Example 10 and Example 3 is that no carbon nanofibers are added in Comparative Example 10, and the rest is the same as Example 3.

[0053] Comparative Example 11: The difference between Comparative Example 11 and Example 3 is that no aluminum-coated glass fiber is added in Comparative Example 11, and the rest is the same as Example 3.

[0054] Comparative Example 12: The difference between Comparative Example 12 and Example 3 is that the mixed raw materials in Comparative Example 12 are not heated and sheared in the extruder, that is, direct melt extrusion in Comparative Example 11, and the rest is the same as Example 3.

[0055] The process of Comparative Example 12 is as follows: The random copolymerized polypropylene, pretreated aluminum-coated glass fiber, carbon nanofiber, 3,5-di(cyclohexylamide)-1-benzoic acid, 1,3,5-benzenetricarboxylic acid tri(aniline), polypropylene grafted maleic anhydride and siloxane are mixed, melt-extruded by an extruder with a barrel temperature of 220°C and a die head temperature of 230°C, and the mixture is fed into a vacuum sizing cooling water tank at a traction speed of 15m / min and the temperature of the cooling water tank is 20°C, and then formed to obtain an antistatic and high-pressure-resistant PPR material.

[0056] The samples prepared in Examples 1 to 3 and the comparative samples in Comparative Examples 1 to 12 were subjected to performance tests. The surface resistivity was based on the GB / T1410-2006 standard. The surface resistivity test samples were treated in a constant temperature and humidity chamber for 48 hours, with a relative humidity of 65±0.2% and a temperature of 23±0.2°C. The tensile strength and elongation at break were tested using the ASTMD638 test standard and test method, and the sample type was Type I. The wear rate was measured using a wear tester, with the sample impact linear velocity of 1.8 m / s and the test time of 1 hour. The test results are shown in Table 1 below.

[0057] Table 1: Performance results

[0058] From the data analysis of Table 1, it can be seen that the present application optimizes the composition and ratio of the PPR material, and combines the process, and the interaction can obtain a PPR material with excellent antistatic effect and mechanical properties that meet the use requirements. The difference between Example 3 and Comparative Examples 1~2 is that the specifications of the aluminum-plated glass fiber are different, but it has a significant effect on the antistatic and mechanical properties of the PPR material, indicating that the addition of aluminum-plated glass fibers of specific specifications in this application has a positive effect on the performance of PPR; the difference between Example 3 and Comparative Examples 3~6 is that the pretreatment (treatment agent) of the aluminum-plated glass fiber is different, but it can also be seen that the aluminum-plated glass fiber after different treatments affects its dispersion in the matrix, and also affects the electrostatic adsorption of the aluminum-plated glass fiber itself. After pretreatment, it can exert its more excellent antistatic effect. The difference between Example 3 and Comparative Examples 7~8 is that the added components of the nucleating agent are different, but it has a significant effect on the mechanical properties and antistatic properties of the PPR material, indicating that the addition of a two-component nucleating agent of a β nucleating agent and an α nucleating agent in this application has a synergistic effect on the performance of the PPR material. The difference between Examples 9 to 11 is that the added components of the PPR material are different (missing components), but they have a significant effect on the mechanical properties and antistatic properties of the PPR material, indicating that the components and proportions of the present application are obtained through creative labor compounding, and are not simply superimposed on the components. The interaction between the components can achieve a more excellent effect. The difference between Example 3 and Comparative Example 12 is that the process is different. It can also be clearly seen that the change in the process and the stable and uniform crystal morphology can significantly affect the mechanical properties of the PPR material. The present application can better control the crystal morphology of the PPR material through step-by-step heating and shearing in the extruder, thereby obtaining a PPR material with better performance.

[0059] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0060] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An anti-static high voltage PPR material, characterized in that: The method comprises the following raw materials in parts by weight: 100 parts of random copolymer polypropylene, 5 to 30 parts of aluminum-coated glass fiber, 1 to 3 parts of carbon nanofiber, 0.1 to 0.3 parts of β-nucleating agent, 0.01 to 0.03 parts of α-nucleating agent, 1 to 3 parts of compatibilizer and 1 to 3 parts of wear-resistant agent; Wherein, the aluminum-plated glass fiber is pre-treated with a treatment agent, and the treatment agent includes a composite antistatic agent and a coupling agent.

2. The antistatic high voltage PPR material according to claim 1, characterized in that: The composite antistatic agent is obtained by mixing ethoxylated amine and graphene oxide in a mass ratio of (0.01-0.08):(1-7).

3. The antistatic high voltage PPR material according to claim 1 is characterized in that: The coupling agent is at least one of γ-glycidyloxypropyltrimethoxysilane, triaminopropyltriethoxysilane and titanate coupling agent.

4. The antistatic high voltage PPR material according to claim 1, characterized in that: The pretreatment is as follows: adding a coupling agent to a glacial acetic acid solution with a mass percentage concentration of 1% to 2%, then adding a composite antistatic agent and mixing to obtain a treatment agent, then adding aluminum-plated glass fiber to the treatment agent, adding a dispersant, and performing ultrasonic dispersion at 85° C. to 100° C. for 10 min to 30 min.

5. The antistatic high voltage-resistant PPR material according to claim 1, characterized in that: The diameter of the aluminum-plated glass fiber is 15 μm-30 μm, the thickness of the aluminum-plated layer is 1 μm-5 μm, and the purity of aluminum is greater than 99%.

6. The antistatic high voltage-resistant PPR material according to claim 5, characterized in that: The specifications of the aluminum-plated glass fiber include grade A, grade B and grade C, wherein the average length of grade A is 5μm~10μm, the average length of grade B is 11μm~25μm, the average length of grade C is 35μm~40μm, and the mass ratio of grade A, grade B and grade C is (1~5):(3~15):(1~3).

7. The antistatic high voltage PPR material according to claim 1, characterized in that: The compatibilizer is polypropylene grafted with maleic anhydride.

8. The antistatic high voltage-resistant PPR material according to claim 1, characterized in that: The anti-wear agent is siloxane, and the molecular weight of the siloxane is in the range of 2w~6w.

9. The antistatic high voltage-resistant PPR material according to claim 4, characterized in that: The dispersant is hexadecyltrimethylammonium bromide.

10. A method for preparing an antistatic high-voltage PPR material, characterized in that: The preparation method is used to prepare the antistatic high-voltage PPR material according to any one of claims 1 to 9, and the preparation method comprises the following steps: The random copolymer polypropylene, aluminum-coated glass fiber, carbon nanofiber, β nucleating agent, α nucleating agent, compatibilizer and wear-resistant agent are mixed, and the temperature is increased to 180°C~220°C at a heating rate of 10°C / min~15°C / min, and the temperature is kept constant for 5min~10min. Then, the temperature is quickly reduced to 100°C~110°C at a cooling rate of 20°C / min~30°C / min, and the temperature is kept constant for 5min~10min, so that the mixed raw materials are heated and sheared in the extruder, and then melt-extruded, cooled, and formed to obtain an antistatic and high-pressure-resistant PPR material.

Citation Information

Patent Citations

  • Preparation method of thermoplastic resin-based composite materials

    CN112011121B

  • Preparation method of antistatic polypropylene material and application of obtained antistatic polypropylene material

    CN117866332A

  • Antistatic plastic pipe, pipe fitting, valve and preparation method of antistatic plastic pipe, pipe fitting and valve

    CN117986752A

  • Thermoplastic high heat conduction shielding composite material and preparation method thereof

    CN108976749A

  • Conductive glass fiber reinforced plastic, conductive glass fiber reinforced plastic plate and preparation method of conductive glass fiber reinforced plastic plate

    CN110669324A